POTENTIAL ANALYSIS AND DEVELOPMENT STRATEGY OF BEEF CATTLE IN CENTRAL JAVA PROVINCE - Utomo, Budi Wihardyanto; Setiadi, Agus; Adiwinarti, Retno (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Central Java Province is one of the provinces with the potential to be a source of beef cattle. The increase in the beef cattle population in Central Java province is expected to increase the national beef cattle population significantly. This study aims to assess the potential of beef cattle and develop a strategy for its development in the Province of Central Java. A study was done using the survey method, and secondary data were obtained from related agencies. Samples were taken using the stratified proportional method as many as 112 farmers. Data were analyzed using LQ analysis, trend analysis, and SWOT analysis. LQ analysis showed that beef cattle's potential base area was in the Grobogan Regency and Kendal Regency. Estimation of beef cattle population in Central Java Province based on trend analysis shows that the areas of Salatiga City, Demak Regency and Grobogan Regency have the potential to become beef cattle base areas. Based on the carrying capacity, areas that can potentially increase livestock populations are Semarang Regency, Salatiga City, and Grobogan Regency. The results of the SWOT analysis show that the right strategy in developing beef cattle is in quadrant I, namely supporting the growth of an aggressive strategy that uses strength to gain opportunities. The recommendation that can be given from this study is that the implementation of strategies in each region will differ according to the potential of each region.